Stakeholder Perspective toward English Language Teaching in Pesantren - M. Zuhri Fakhruddin; Fika Megawati (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2018)
In the teaching and learning activity, condusivity and effectivity are determined by various factors, such teacher and students’ behavior, teaching instrument, methodology and material structure. Each stakeholder may have different perspective upon these various aspects and –perhaps- will significantly influence their behavior toward the activity of teaching and learning. In a premise that a positive behavior and constructive collaboration is built on a linier perspective among stakeholders, this small scale research intends to investigate stakeholders’ perspective upon English Language Teaching in Pesantren Bilingual Al Amanah, Junwangi, Krian. Through a direct structured interview with stakeholders (teacher, head of language enforcement, and some representative students), researcher collects the data to be analyzed, interpreted and presented in an analytical descriptive report. The finding will be significant toward the foundation of stakeholders’ harmonization, enhancement of teaching method, development of English Language Teaching program in Pesantren as well as a milestone of further research and innovation.